Riverine influence determines nearshore heterogeneity of nutrient (C, N, P) content and stoichiometry in the KwaZulu-Natal Bight, South Africa. (1st June 2016) - Scharler, UM; Ayers, MJ; de Lecea, AM; Pretorius, M; Fennessy, ST; Huggett, JA; MacKay, CF; Muir, D
Abstract : Riverine influences on nearshore oceanic habitats often have detrimental consequences leading to algal blooms and hypoxia. In oligo- to mesotrophic systems, however, nutrient delivery via rivers may stimulate production and even be a vital source of nutrients, as may nutrient supplements from upwelling. We investigated the nutrient content (C, N, P) and stoichiometry of sediment, and several pelagic, benthopelagic and benthic species in the KwaZulu-Natal (KZN) Bight, a narrow shelf area on the south-east coast of South Africa, bordering the Agulhas Current. Three suggested nutrient sources to the bight are the Thukela River in the central region of the bight, upwelling in the northern part and a semi-permanent eddy (Durban Eddy) in the southern part. Elemental content of the various groups studied showed significantly higher values for most groups at the site near the Thukela River. C:P and N:P were highest in the southern part of the bight, and lowest near the Thukela Mouth or at Richards Bay in the north, indicating the latter were the P-richer sites. Sediment organic matter showed lowest elemental content, as expected, and zooplankton stoichiometry was highest compared to all other biotic groups. Environmental heterogeneity played a greater role in organismal C, N and P content and stoichiometry compared to phylogeny, with the exception of the differences in C:P and N:P of zooplankton. From this bight-wide study, the higher elemental content and lower ratios at the Thukela Mouth site supported previous findings of the importance of coastal nutrient sources to the bight ecosystem. Reductions in river flow for water use in the catchment areas may therefore have negative consequences for the productivity of the entire ecosystem.